A pragmatic approach to children with suspected shunt and cerebrospinal fluid device infection. Issue 10 (October 2022) - Hollingworth, Milo; Bird, David; Crusz, Shanika A.; Kirkman, Matthew A.; Vyas, Harish
Abstract: Cerebrospinal fluid (CSF) shunts and devices are commonly encountered in paediatric practice. Meningitis, ventriculitis and acute hydrocephalus are potentially life-threatening complications of an infected indwelling CSF device and may require emergency neurosurgical intervention. Suspicion of infection in a child with a CSF device is a common problem for neurosurgeons, paediatricians, and generalists alike. Diagnosis requires a thorough understanding of why, when, where and what device was implanted and prompt identification of risk factors for infection including recent surgery and young age. The utility of diagnostic tests depends on the pre-test probability of infection and expert consideration of the whole clinical picture. Treatment is based on surgical removal of the device, where feasible, and tailored microbiological therapy followed by device re-implantation if, and when, required. This review describes the risk factors for device infection, the role of neurosurgery and microbiology in the management of the disease. In this updated review article, we propose an investigation and treatment approach to guide clinicians in managing these challenging patients from presentation to discharge.